Compulsory Voting and Electoral Participation of Latin American Migrants in Belgium, Luxemburg and the Netherlands - Umpierrez de Reguero, Sebastián; Dandoy, Régis (Politics of the Low Countries, 2025)
An increasing number of countries have granted electoral rights to their citizens living abroad. An understanding of the different dimensions of the electoral behaviour of migrants and the institutional characteristics of their countries of origin and residence is crucial for their political integration and (re-)socialization. Based on an aggregate-level design, this article evaluates the impact of compulsory voting on non-resident citizens’ voter turnout taking into account both origin and residence country contexts, providing insights into the dual context of political transnationalism. It explores the participation of Latin American migrants residing in Belgium, Luxemburg and the Netherlands in all their national and supranational elections since 2005, creating singular electoral environments where the voting obligation varies in the countries of origin and residence. The article finds that compulsory voting has a positive impact on non-resident citizens’ voter turnout and suggests trends of analysis of prospective electoral behaviour in a dual institutional context.